Primary ovarian malignant mixed mullerian tumors / carcinosarcomas: a clinico-pathological and immunohistochemical analysis of four cases and review of literature - Badyal, Rama K; Dey, Pranab (Annals of Pathology and Laboratory Medicine, 2015)
Ovarian carcinosarcomas (OCS), also known as malignant mixed mullerian tumors (MMMTs) are among the rarest and most challenging malignancies arising from the female genital tract. This tumor is estimated to account for only 1-3% of all ovarian malignancies. The influence of proportion of the malignant epithelial or sarcomatous component on the disease progression is a matter of debate. Herein, we analysed clinico-pathological and immunohistochemical features of four cases of ovarian carcinosarcomas diagnosed over a period of seven years from 2008-2014. All the patients were post-menopausal with a mean age of 59.25 years. Carcinomatous component was high grade serous in three cases and high grade endometroid in one case. CK and EMA immunostains were used to highlight carcinomatous component while vimetin immunostain highlighted sarcomatous areas. Two patients had heterlogous sarcomatous components; rhabdomyosarcomatous and chondromatous areas which were highlighted by Myogenin, desmin and S-100 respectively. Immunohistochemistry is an essential ancillary technique in highlighting biphasic nature and areas of heterologous differentiation which may have a prognostic impact. The patients were treated with optimal debulking surgery followed by adjuvant platinum/taxane or platinum/ifosfamide combinations based chemotherapy.